1995
DOI: 10.1063/1.1146493
|View full text |Cite
|
Sign up to set email alerts
|

Distributed temperature sensor using holmium-doped optical fiber and spread-spectrum techniques

Abstract: This paper describes the feasibility analysis of using Holmium-doped single-mode fiber and spread-spectrum techniques to monitor a temperature distribution in the cryogenic range. An optimized holmium-doped fiber was realized and thermally characterized. For probing the sensitive fiber we realized an optical time domain reflectometer using pseudorandom sequences to improve the dynamic range at the operating wavelength and to obtain both rapid response time and high spatial resolution. The system, tested over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Rare-earth materials like holmium, erbium, ytterbium, and praesodymium show high sensitivity for utilization in DTS systems. Yataghene et al [15] reported high thermal sensitivity of holmium-doped optical fibers. Holmium ions show best thermal sensitivity in cryogenic temperature range, around 650 nm [15].…”
Section: Use Of Rare Earth Ionsmentioning
confidence: 99%
“…Rare-earth materials like holmium, erbium, ytterbium, and praesodymium show high sensitivity for utilization in DTS systems. Yataghene et al [15] reported high thermal sensitivity of holmium-doped optical fibers. Holmium ions show best thermal sensitivity in cryogenic temperature range, around 650 nm [15].…”
Section: Use Of Rare Earth Ionsmentioning
confidence: 99%
“…To achieve spatial resolution, the same principles of signal generation and processing can be used as in radar measurement and fault finding in fiber-optic communication networks . In fact, these methods have already been employed for spatially resolved sensing of physical parameters such as magnetic, electric, and acoustic fields, temperature, strain, stress, pressure, displacement, ionizing radiation, and others. , Alternative methods for distributed, spatially resolved measurement of physical parameters include optical time-domain reflectometry (based on Rayleigh, Raman, and Brillouin scattering, fluorescence, polarization, and attenuation), transmissive frequency-modulated carrier wave, optical frequency- domain reflectometry, and optical amplification by a counterpropagating pump pulse . A critical analysis of these and less common techniques shows that optical time-domain reflectometry is particularly attractive for distributed chemical monitoring.…”
Section: Principle Of Spatially Resolved Distributed Analyte Measurem...mentioning
confidence: 99%
“…However, most of the standard thermometry methods tend to fail at cryogenic and below room temperatures where novel temperature measurement principles are needed. Studies on luminescence thermometry [2,3] at cryogenic and low temperatures mainly employ Mn 2+/4+ and Eu 3+ -activated phosphors or upconversion materials [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%